Biomechanical and Clinical Study of Rod Curvature in Single-Segment Posterior Lumbar Interbody Fusion - Han, Lin; Li, Yongheng; Li, Zhiyong; Ma, Hongdao; Wang, Chenfeng; Chen, Qiang; Lu, Xuhua (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Pedicle screw fixation is a common technique in posterior lumbar interbody fusion (PLIF) surgery for lumbar disorders. During operation, rod contouring is often subjective and not satisfactory, but only few studies focused on the rod-contouring issue previously. This study aims to explore the effect of the rod contouring on the single-segment PLIF by finite element (FE) method and retrospective study. Methods: FE model of the L1-S1 vertebrae was first reconstructed, and subsequently single-segmental (L4/5) PLIF surgeries with four rod curvatures (RCs) were simulated. Herein, three RCs were designed by referring to centroid, Cobb and posterior tangent methods applied in lumbar lordosis measurement, and zero RC indicating straight rods was included as well. Clinical data of patients subjected to L4/5 segmental PLIF were also analyzed to verify the correlation between RCs and clinical outcome. Results: No difference was observed among the four RC models in the range of motion (ROM), intersegmental rotation angle (IRA), intradiscal pressure (IDP) under four actions. Posterior tangent model had less maximum stress in fixation (MSF) in flexion, extension and axial rotation compared to the other RC models. Patients with favorable prognosis had larger RC and positive RC minus posterior tangent angle of fused segments (RC-PTA) with respect to those who had poor prognosis and received revision surgery. Conclusions: All RC models had similar biomechanical behaviors under four actions. Posterior tangent-based RC model was superior in fixation stress distribution compared to centroid, Cobb and straight models. The retrospective study demonstrated that moderate RC and positive RC-PTA were associated with better postoperative results.